1996
DOI: 10.1007/bf01799417
|View full text |Cite
|
Sign up to set email alerts
|

Progressive generalized brain atrophy and infantile spasms associated with cytochromec oxidase deficiency

Abstract: Summary Large neutral amino acids (LNAA) have been used on a limited number of patients with phenylketonuria (PKU) with the purpose of decreasing the influx of phenylalanine (Phe) to the brain. In an open‐label study using LNAA, a surprising decline of blood Phe concentration was found in patients with PKU in metabolic treatment centres in Russia, the Ukraine, and the United States. To validate the data obtained from this trial, a short‐term double‐blind placebo control study was done using LNAA in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…As LSFC patients are the largest known cohort with a genetically homogeneous, nuclear encoded congenital lactic acidosis studied,1 further investigation is required into the new phenotypically distinct forms of Leigh syndrome caused by different mutations in the LRPPRC gene. Nevertheless, there is a similar case presentation to the above described by Bakker et al ; a newborn presenting with tachypnoea, feeding difficulties, severe lactic acidosis and a high pyruvate level 5. It could be hypothesised that certain genetic mutations could thus present initially with an elevated pyruvate kinase level, which could be used as an indicator for further investigation into Leigh’s syndrome.…”
Section: Discussionsupporting
confidence: 63%
“…As LSFC patients are the largest known cohort with a genetically homogeneous, nuclear encoded congenital lactic acidosis studied,1 further investigation is required into the new phenotypically distinct forms of Leigh syndrome caused by different mutations in the LRPPRC gene. Nevertheless, there is a similar case presentation to the above described by Bakker et al ; a newborn presenting with tachypnoea, feeding difficulties, severe lactic acidosis and a high pyruvate level 5. It could be hypothesised that certain genetic mutations could thus present initially with an elevated pyruvate kinase level, which could be used as an indicator for further investigation into Leigh’s syndrome.…”
Section: Discussionsupporting
confidence: 63%
“…Limited attention has been given to the role of mitochondrial disease in infantile spasms. The association between spasms and mitochondrial disorders has been reported mainly in the form of case reports (Boor et al, 1992;Pastoris et al, 1993;Makela-Bengs et al, 1994;Bakker et al, 1996;Verdu et al, 1996). However, a recent study on epileptic phenotypes asssociated with mitochondrial disorders found spasms in 17% of patients (Canafoglia et al, 2001).…”
Section: Discussionmentioning
confidence: 99%